2020
DOI: 10.3233/wor-203278
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary lifestyle among office workers and coronary heart disease risk factors due to the COVID-19 quarantine

Abstract: The COVID-19 pandemic has affected the entire world. It is difficult to follow protocols and regulations set forth by governments, designed by the World Health Organization. The most common protocol set forth by governments is quarantining at home. Many occupations must stay home to comply with this protocol. Among these occupations, office workers are the most common group to comply and work from home. This has led to a lack of daily movement and increased sedentary lifestyle, which has made employees prone t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…However, further research is needed to clarify how to reduce the health risks and increase the benefits of working from home. Interventions aimed at decreasing cardiovascular disease risk that can easily be integrated into the daily life of employees working from home are reported in Figure 3 [68]. It is suggested to address possible psychological and physical issues linked to working from home [69] and to timely implement tailored measures prior to initiating working from home in order to minimize potential negative effects of this transition.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…However, further research is needed to clarify how to reduce the health risks and increase the benefits of working from home. Interventions aimed at decreasing cardiovascular disease risk that can easily be integrated into the daily life of employees working from home are reported in Figure 3 [68]. It is suggested to address possible psychological and physical issues linked to working from home [69] and to timely implement tailored measures prior to initiating working from home in order to minimize potential negative effects of this transition.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In this respect, accurate health information and an understanding of the relationships between psychosocial determinants and physical activity level could be useful to the institution in implementing a health promotion program for these workers; (2) ELDAF includes a broad range of workers (blue- and white-collar workers), warranting the inference that future findings may achieve appropriate levels of external validity; (3) part of the ELDAF population lives in a rural area. Considering that scientific information on physical activity determinants in rural populations are scarce, the study will naturally contribute to the literature; and (4) follow-up starting right after a public health crisis that has had considerable impact on various aspects of people’s lives worldwide, including lifestyle and work conditions, may be significant, given that recent studies have shown worsening indicators of both lifestyle and occupational health [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CCVD SMR of CLK was the highest in 1997–2011 but only slightly higher in suicide for the same period. CLK, a typically sedentary job, is known to have a higher risk of CCVD [ 28 ].…”
Section: Discussionmentioning
confidence: 99%